ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI KONSUMEN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA WARUNG SEBLAK PRASMANAN MIMBAAN SITUBONDO - Fadilah, Moch.; Sari, Lita Permata; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
In the current era of globalization, business competition is fierce, where each company is required to meet consumer demand and create products that are unique and different from other competitors. Therefore, the company's efforts to develop new products can be an effective strategy for companies to seek as much profit or profit as possible. The purpose of this study was to analyze the factors that influence consumer buying interest through customer satisfaction as an intervening variable at Warung Seblak Prasmanan Mimbaan Situbondo. The target respondents of this study were consumers of Warung Seblak Prasmanan Mimbaan using the simple random sampling method. Data and hypothesis analysis using the Structural Equation Model-Partial Leas Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that price has a significant positive effect on customer satisfaction. Service quality has a positive but insignificant effect on customer satisfaction. Consumer trust has a significant positive effect on customer satisfaction. Price has a positive but insignificant effect on consumer buying interest. Service quality has a significant positive effect on consumer buying interest. Consumer trust has a positive but insignificant effect on consumer buying interest. Customer satisfaction has a significant positive effect on consumer buying interest. Price has a significant positive effect on consumer buying interest through customer satisfaction through customer satisfaction. Service quality has a positive but insignificant effect on consumer buying interest through customer satisfaction. Consumer confidence has a significant positive effect on consumer buying interest through customer satisfaction.